2018
DOI: 10.1021/acs.joc.8b01002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of 2′-OMe-RNAs Modified with Cross-Linkable 7-Deazaguanosine Derivatives

Abstract: Cross-linkable 7-deaza-6-vinylguanosine (ADVP) and 7-propynyl-7-deaza-6-vinylguanosine (ADpVP) derivatives were synthesized and successfully incorporated into 2'-OMe-RNA oligonucleotides by solid-phase oligonucleotide synthesis. Analysis of their cross-link properties revealed that the 7-propynyl substituent on ADpVP induces a significant enhancement of the cross-link kinetics of the proximal 6-vinyl group to the complementary uracil base in the target RNA compared to that of ADVP. In addition, the 2'-OMe-RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…2). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] We initially developed a 2-amino-6-vinylpurine (AVP) base as a covalent warhead (Fig. 2A).…”
Section: Creation Of Interstrand Crosslinking Structuresmentioning
confidence: 99%
“…2). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] We initially developed a 2-amino-6-vinylpurine (AVP) base as a covalent warhead (Fig. 2A).…”
Section: Creation Of Interstrand Crosslinking Structuresmentioning
confidence: 99%
“…Lastly, Basic Protocol 3 shows an example of the RNA‐targeting crosslinking experiment using ADpVP‐RNA. All characterization and RNA‐crosslink data described in the article are based on a previously published report (Yamada et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Basic Protocol 3 shows an example of the RNA-targeting crosslinking experiment using ADpVP-RNA. All characterization and RNA-crosslink data described in the article are based on a previously published report (Yamada et al, 2018). Sodium bicarbonate (NaHCO 3 ) Sodium chloride (NaCl) Sodium sulfate (Na 2 SO 4 ) Hexane (e.g., Junsei Chemical) Chloroform (CHCl 3 , e.g., Junsei Chemical) Sodium methoxide (NaOMe) Methanol (MeOH), anhydrous (e.g., Wako Pure Chemical Industries) Ethyl acetate (EtOAc) Methanol (MeOH, e.g., Junsei Chemical) Dimethylformamide (DMF), anhydrous (Wako Pure Chemical Industries) Sodium hydride (NaH, 60% in mineral oil; e.g., Wako Pure Chemical Industries) Iodomethane (CH 3 I) 1,4-Dioxane 2 M aqueous sodium hydroxide (NaOH) 2 M aqueous hydrogen chloride (HCl) tert-Butyldimethylsilyl chloride (TBDMSCl, e.g., Tokyo Chemical Industry) Imidazole Tetrakis(triphenylphosphine)palladium (0) (Pd(PPh 3 ) 4 , e.g., Wako Pure Chemical Industries) Copper(I) iodide (CuI, e.g., Wako Pure Chemical Industries) 1,1,1,3,3,3-Hexamethyldisilazane (HMDS, e.g., Wako Pure Chemical Industries) Propyne (e.g., Wako Pure Chemical Industries) Acetonitrile (e.g., Junsei Chemical) Diethyl ether (Et 2 O, e.g., Junsei Chemical) Dichloromethane (CH 2 Cl 2 ), anhydrous (e.g., Wako Pure Chemical Industries) Triethylamine (Et 3 N, e.g., Wako Pure Chemical Industries) 4-Dimethylaminopyridine (DMAP, e.g., Wako Pure Chemical Industries) p-Toluenesulfonyl chloride (p-TsCl, e.g., Tokyo Chemical Industry) 1,4-Dioxane, anhydrous (e.g., Wako Pure Chemical Industries) Potassium carbonate (K 2 CO 3 , e.g., Wako Pure Chemical Industries) Vinylboronic anhydride pyridine complex (e.g., Sigma Aldrich) Dichlorobis(triphenylphosphine)palladium (II) (PdCl 2 (PPh 3 ) 2 , e.g., Wako Pure Chemical Industries) Sodium thiomethoxide (NaSMe, e.g., Sigma Aldrich) Pyridine, anhydrous (e.g., Wako Pure Chemical Industries) Toluene, anhydrous (e.g., Wako Pure Chemical Industries) Phenoxyacetyl chloride (PacCl, e.g., Tokyo Chemical Industry) Tetrahydrofuran (THF), anhydrous (e.g., Wako Pure Chemical Industries) 1.0 M tetrabutylammonium fluoride (TBAF) solution in THF (e.g., Sigma Aldrich) 4,4 -Dimethoxytrityl chloride (DMTrCl, e.g., Tokyo Chemical Industries) N,N-Diisopropylethylamine (DIPEA, e.g., Wako Pure Chemical Industries) 2-Cyanoethyl-N,N -diisopropylchlorophosphoramidite (e.g., Wako Pure Chemical Industries) Nitrogen (N 2 ) or argon gas Dry ice Acetone (e.g., Junsei Chemicals) Silica gel 60 N (spherical, neutral, 100 to 210 μm; Kanto Chemical) Silica gel 60 N (spherical, neutral, 40 to 50 μm; Kanto Chemical) Phosphorus pentoxide (P 2 O 5 , e.g., Wako Pure Chemical Industries) Electronic balance (e.g., Mettler Toledo) Merck thin-layer chromatography (TLC) silica plates (60 F 254 ; 0.25 mm thick) UV lamp (254 nm) Yamada et al…”
Section: Introductionmentioning
confidence: 99%
“…A crosslink method without using such external stimuli would allow milder reaction conditions and lower the usage limitations of this type of technology. We have been studying a crosslink strategy that does not require the external stimuli-driven activation but proceeds only by sequence specific hybridization with target DNA and RNA based on the utility of proximity effect with complementary nucleobases(Hagihara et al, 2013;Hattori, Hirohama, Imoto, Kusano, & Nagatsugi, 2009;Imoto et al, 2010;Kusano et al, 2015;Nagatsugi & Imoto, 2011;Nagatsugi, Kawasaki, Usui, Maeda, & Sasaki, 1999;Yamada et al, 2018).It has been reported that the AMO containing crosslinked double-stranded RNA at terminal position can efficiently inhibit the target miRNAs(Mie et al, 2018). By using the CFO containing AVP, we have efficiently prepared the miR21-targeting AMOs bearing the crosslinked duplex.…”
mentioning
confidence: 99%